Prolonged antibiotic prophylaxis in tissue reconstruction using autologous fat grafting: Is there a benefit for wound healing?. Issue 2 (9th June 2021) - Morandi, Evi M.; Winkelmann, Selina; Dostal, Lucie; Radacki, Isabel; Rieger, Ulrich M.; Bauer, Benedikt; Verstappen, Ralph; Wolfram, Dolores; Bauer, Thomas
Abstract: Fat grafting is a well‐established method in plastic surgery. Despite many technical advances, standardised recommendations for the use of prophylactic antibiotics in fat grafting are not available. This retrospective multicentre study aims to analyse the use of prophylactic antibiotics in fat grafting and to compare complication rates for different protocols. A retrospective medical chart review of 340 patients treated with fat grafting of the breast from January 2007 to March 2019 was performed in three plastic surgery centres. Complications, outcomes, and antibiotic regimes were analysed. The Clavien‐Dindo classification was applied. All patients received perioperative antibiotic prophylaxis: 33.8% (n = 115) were treated with a single shot (group 1), 66.2% (n = 225) received a prolonged antibiotic scheme (group 2). There was no significant difference in the number of sessions ( P = .475). The overall complication rate was 21.6% (n = 75), including graft resorption, fat necrosis, infection, and wound healing problems. Complication rates were not significantly different between groups. Risk factors for elevated complication rates in this specific patient group are smoking, chemotherapy, and irradiation therapy. The complication rate for lipografting of the breast is low, and it is not correlated to the antibiotic protocol. The use of prolonged prophylactic antibiotics does not lower the complication rate.